Evaluation of technology of artisanal and improved production of Vitellaria paradoxa butter in Burkina Faso - Zida, Issouf; Tapsoba, François; Tarnagda, Bakary; Zio, Souleymane; Savadogo, Aly (International Journal of Advances in Applied Sciences, 2023)
This study aims to find the current various processes for the almond producers and the extractors of shea butter in Burkina Faso. The survey was conducted in seven provinces. Three approaches to data gathering were used: group interviews in which forms were filled out during interviews; individual interviews in which the interviewer asked one person about the survey-related tasks; and semi-structured group interviews. The survey data were analyzed and the results obtained made it possible to draw up four technological diagrams of almond products and three of almond processing into butter. The surveys showed that shea kernels were produced by boiling, pit fermented, and then smoked, or only smoked. In terms of butter making, the classic churning and roasting processes were used. These results revealed that the processes of butter making and processing are not uniform in all the units of producers. However, further studies are recommended, especially to determine the physico-chemical, sensory, and microbiological parameters of the butter from the productions to better appreciate their qualities.